2005
DOI: 10.1128/aac.49.6.2460-2466.2005
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules VP-14637 and JNJ-2408068 Inhibit Respiratory Syncytial Virus Fusion by Similar Mechanisms

Abstract: Here we present data on the mechanism of action of VP-14637 and JNJ-2408068 (formerly R-170591), two small-molecule inhibitors of respiratory syncytial virus (RSV). Both inhibitors exhibited potent antiviral activity with 50% effective concentrations (EC 50 s) of 1.4 and 2.1 nM, respectively. A similar inhibitory effect was observed in a RSV-mediated cell fusion assay (EC 50 ‫؍‬ 5.4 and 0.9 nM, respectively). Several drug-resistant RSV variants were selected in vitro in the presence of each compound. All selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 23 publications
4
67
0
Order By: Relevance
“…Characterization of the hit compound in infection and subinfection reporter assays and tracing of resistance to point mutations in the viral F protein confirmed interference with an F-mediated membrane merger as the underlying mechanism of anti-RSV activity. The RSV entry machinery emerges as highly susceptible to inhibition by small-molecule inhibitors, because structurally distinct lead compounds identified in several independent drug discovery campaigns all block membrane fusion (21)(22)(23)(24). Possible reasons for this prevalence may include that entry inhibition poses lower demands on the compound than other inhibition strategies, because it does not mandate plasma membrane permeability of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Characterization of the hit compound in infection and subinfection reporter assays and tracing of resistance to point mutations in the viral F protein confirmed interference with an F-mediated membrane merger as the underlying mechanism of anti-RSV activity. The RSV entry machinery emerges as highly susceptible to inhibition by small-molecule inhibitors, because structurally distinct lead compounds identified in several independent drug discovery campaigns all block membrane fusion (21)(22)(23)(24). Possible reasons for this prevalence may include that entry inhibition poses lower demands on the compound than other inhibition strategies, because it does not mandate plasma membrane permeability of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…S7). In addition to these two classes, resistance hotspots were determined also for the remaining three scaffolds and, in analogy to our characterization of GPAR-3710, in all cases included F residues in the 400 and/or 489 microdomains (22,24). Although recognized as surprising that distinct chemical inhibitor classes supposedly target the same F microdomain with high affinity (30), previous studies concluded that all of these diverse compounds prevent RSV entry through docking into the same hydrophobic cavity around residue Y198 in the central HR-A triple helix (21,30), which emerges transiently during assembly of the 6HB structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, it is recognized that RSV-F is a protein that mediates the fusion of viral envelope with host cell membrane and is regarded as a prominent target for therapeutic intervention [26][27][28]. A previous molecular docking study showed that 3,4-DCQA binds RSV-F well.…”
Section: Introductionmentioning
confidence: 99%